Variation in limits to germination temperature and rates across the seed-seedling transition in the palm Oenocarpus bataua from the Brazilian Amazon - Bastos, L. L.S. (Seed Science and Technology, 2020)
Germination efficiency can be quantified using the optimal temperature and the temperature limits for germinating seeds. Such estimates generally pertain to the earliest phase of germination, that of radicle emergence. Few comparisons have been made on the subsequent stages of growth, even though the seed-seedling transition is critical for establishment. We assessed the thermal parameters for development of four developmental stages over the seed-seedling transition (germination button, primary root, 1st cataphyll and 2nd cataphyll) in the Amazonian palm tree Oenocarpus bataua. Germination was observed under eight constant and two alternating temperatures with four replicates of 25 seeds for each condition. Constant temperatures of 25 and 30°C resulted in the highest final germination in the shortest time period for all four germination criteria. Alternating temperatures did not enhance germination and seedling development. The four germination stages differed in temperature tolerances. While the germination button formed over a large range of constant temperatures (10 to 40°C), development of the 2nd cataphyll (i.e., seedling development) over 60 days was limited to 25 to 30°C. These results indicate that the thermal responses for growth in this species vary with developmental stage and that early seedling growth, when seed reserves are being mobilised, occurs over the most restricted range of temperature across the four stages of development.